Organizational and methodological aspects of the formation and development of the professional competences of future officers of the NGU in the conditions of the martial state - Ktitorov, Maksym (Scientific notes of the pedagogical department, 2022)
The article is devoted to one of the urgent problems of the study of the formation and development of professional competences of future officers of the NGU in the conditions of martial law. An analysis of the key concepts of the research «professional competence», «professional competence of future officers of the NGU» was carried out. The main requests of modern society to the personality of a military serviceman are outlined. The organizational and methodological aspects of the formation and development of professional competences of future officers of the NGU in the conditions of martial law were defined and substantiated. A complex of general scientific methods of conducting the research was used, such as: the method of analysis and synthesis; scientific abstraction, induction and deduction; project method. The key professional competencies of future officers of the NGU have been determined, including: civil; administrative and informational; communicative; individual and psychological; socio-legal; moral and ethical; general military, tactical, tactical-special; psychological and pedagogical; military and technical. It has been proven that the successful formation and development of professional competence of future officers of the NGU in the conditions of martial law will be carried out under the condition of compliance with organizational and methodological aspects. The component structure of the author’s scheme of the approximate model of the formation of professional competence of future officers of the NGU in the conditions of martial law has been developed and substantiated.